A Bibliometric Analysis of 3D Printing in Personalized Medicine Research from 2012 to 2022 - Aile Xue; Wenjie Li; Wenxiu Tian; Minyue Zheng; Lan Shen; Yanlong Hong (MDPI AG, 2023)
In recent years, the 3D printing of personalized drug formulations has attracted the attention of medical practitioners and academics. However, there is a lack of data-based analyses on the hotspots and trends of research in this field. Therefore, in this study, we performed a bibliometric analysis to summarize the 3D printing research in the field of personalized drug formulation from 2012 to 2022. This study was based on the Web of Science Core Collection Database, and a total of 442 eligible publications were screened. Using VOSviewer and online websites for bibliometric analysis and scientific mapping, it was observed that annual publications have shown a significant growth trend over the last decade. The United Kingdom and the United States, which account for 45.5% of the total number of publications, are the main drivers of this field. The International Journal of Pharmaceutics and University College London are the most prolific and cited journals and institutions. The researchers with the most contributions are Basit, Abdul W. and Goyanes Alvaro. The keyword analysis concluded that the current research hotspots are "drug release" and "drug dosage forms". In conclusion, 3D printing has broad application prospects in the field of personalized drugs, which will bring the pharmaceutical industry into a new era of innovation.